2009
DOI: 10.3748/wjg.15.1901
|View full text |Cite
|
Sign up to set email alerts
|

A case of primary isolated non-Hodgkin’s lymphoma of the esophagus in an immunocompetent patient

Abstract: Primary non-Hodgkin's lymphoma of the esophagus is a rare disease. A case of primary isolated nonHodgkin's lymphoma of the esophagus in a 77-yearold man without acquired immunodeficiency syndrome is presented. We describe the clinical features and the imaging findings (barium swallow, endoscopic ultrasonography and CT) of a biopsy proven B-cell lymphoma with diffuse transmural involvement of the esophagus wall, which was discovered incidentally. We also briefly review the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…The esophagus is the least commonly involved gastrointestinal organ, accounting for less than 1 % of patients with primary gastrointestinal lymphoma [1]. Extranodal natural killer (NK)/T cell lymphoma of true natural killer cell origin is extremely rare, with only a few case reports in the literature [2,3]. In this case, the endoscopic picture showed mucosal erythema, a mass with ulceration, and wall thickness, similarly to previous reports of esophageal lymphoma.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…The esophagus is the least commonly involved gastrointestinal organ, accounting for less than 1 % of patients with primary gastrointestinal lymphoma [1]. Extranodal natural killer (NK)/T cell lymphoma of true natural killer cell origin is extremely rare, with only a few case reports in the literature [2,3]. In this case, the endoscopic picture showed mucosal erythema, a mass with ulceration, and wall thickness, similarly to previous reports of esophageal lymphoma.…”
supporting
confidence: 72%
“…In a previous study, esophageal lymphoma showed lymphomatous involvement of the gastrointestinal wall to produce a typical hypoechoic transmural thickening [4], such as in this case. However, another report described imaging of a submucosal, heterogeneous, mainly hyperechoic mass [2]. …”
mentioning
confidence: 99%
“…Unfortunately, esophageal lymphoma defines acquired immune deficiency syndrome and is associated with a poor prognosis [10]. Conversely, B-cell lymphoma is a positive prognostic factor [11,12]. In our experience, 4 patients had resection of an esophageal lymphoma.…”
Section: Commentmentioning
confidence: 92%
“…NHL previously accounted for approximately 3% of AIDS-defining clinical conditions, but this proportion had declined. The incidence of PCNS lymphoma was highest; other types of lymphomas appear as case reports in the literature (Rich et al, 1992;Cappell and Botros, 1994;Rizzi et al, 2001;Doweiko et al, 2004;Khan et al, 2006;Mohan et al, 2007;Mani et al, 2008;Rezende et al, 2009;Kalogeropoulos et al, 2009;Li and Cheng, 2011). Previously, NHL accounted for approximately 3% of AIDS-defining clinical conditions, but this percentage has declined.…”
Section: The Imaging Features Of Aids-related Non-hodgkin's Lymphomamentioning
confidence: 93%